(untitled) (Experimental biology, 2025)
The study examines the ecological and geographical characteristics of Astragalus ammodendron, a typical species of desert ecosystems in Central Asia. The species is distributed in Kazakhstan, Uzbekistan, Turkmenistan, and China, preferring sandy and clay deserts, where it forms stable phytocenoses. The aim of the study is to analyze the ecological and geographical plasticity of A. ammodendron, its adaptive mechanisms, and its role in ecosystem stabilization. The research employs route reconnaissance, ecological-systematic, and ecological-geographical methods. A comparative analysis of contemporary and historical herbarium data from collections in Kazakhstan, Russia, and Uzbekistan was conducted, along with cartographic modeling of the species’ range using QGIS 3.34. The obtained data confirm the species’ drought resistance, its ability to stabilize sandy substrates, and its formation of specific communities with Haloxylon aphyllum, Calligonum leucocladum, and Artemisia terrae-albae. In some areas, population fragmentation has been observed due to anthropogenic factors, including livestock grazing and changes in the hydrological regime. This study contributes to understanding the ecological and geographical patterns of desert plants and their phytocenotic role. The practical significance of the results lies in their potential application for monitoring, conservation, and restoration of ecosystems undergoing degradation due to climate change and anthropogenic impact.